Dinitrogen Fixation: Rationalizing Strategies Utilizing Molecular Complexes. Issue 12 (29th December 2020) - Masero, Fabio; Perrin, Marie A.; Dey, Subal; Mougel, Victor
Abstract: Dinitrogen (N2 ) is the most abundant gas in Earth's atmosphere, but its inertness hinders its use as a nitrogen source in the biosphere and in industry. Efficient catalysts are hence required to ov. ercome the high kinetic barriers associated to N2 transformation. In that respect, molecular complexes have demonstrated strong potential to mediate N2 functionalization reactions under mild conditions while providing a straightforward understanding of the reaction mechanisms. This Review emphasizes the strategies for N2 reduction and functionalization using molecular transition metal and actinide complexes according to their proposed reaction mechanisms, distinguishing complexes inducing cleavage of the N≡N bond before (dissociative mechanism) or concomitantly with functionalization (associative mechanism). We present here the main examples of stoichiometric and catalytic N2 functionalization reactions following these strategies. Abstract : Dinitrogen (N2 ) is the most abundant gas in the Earth's atmosphere, but its inertness hinders its use as a nitrogen source in the biosphere and in industry. This review emphasizes the strategies for N2 reduction and functionalization using molecular transition metal and actinide complexes according to their proposed reaction mechanisms and presents the main examples of stoichiometric and catalytic N2 functionalization reactions.